Between Creed and Qur’ān: Shi’ite Views of ‘Iṣmah in Light of Qur’ān (48:1‒2) (American Journal of Islam and Society, 2012)
Islam’s main document, the Qur’ān, is perceived as the foundation for thereligion’s creedal ideas. Throughout the ages, however, Qur’ānic exegesis(tafsīr), like its counterpart endeavors in other established religions, hasbecome subject to circularity. This means basically that while faith-basedscholars may declare that their exegeses are based upon reading scripturequa scripture, their interpretations are often conditioned by creedal constructsimposed upon the text. One such issue in Islam revolves around‘iṣmah, the concept of prophetic inerrancy.A prophet, in the Islamic worldview, is not simply someone who deliversGod’s message, but one who is also tasked with being an exemplar.Since the holder of such an office must have impeccable conduct,as well as proficiency in teaching and explaining what God wants for thefaith community, it might be assumed that a doctrine of prophetic inerrancywas a logical inevitability. There is a general agreement betweenSunnis and Shīʻahs—primarily by rational analysis—on the issue of theProphet (ṢAAS) being inerrant from major and minor sins. The conceptis not clearly spelled out in the Qur’ān, and based on their differences increedal perception, the two groups, while agreeing on a core idea, differ oncertain details ...